TINJAUAN METODE AUDITORY, INTELLECTUALLY, AND REPETITION (AIR) PADA PELAGUAN MATA PELAJARAN BAHASA ARAB DI MADRASAH DINIYAH ROUDLATUT THOLIBIN DESA JRAGANAN - Ayu Puji Lestari; Denis Setiaji (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Today, the world of education has used a lot of singing methods in studying material,  one of which is Madrasah Diniyah Roudlatut Tholibin at Jraganan Village.  The singing method carried out, specifically in Arabic subjects in grades one and two, was translated into Javanese.  This song is allegedly related to the Auditory, intellectually, and Repetition (AIR) learning model.  To prove this, this research uses qualitative research methods through observation, interviews, and literature study.  This search aims to reveal the signal of the link between the learning methods at the madrasah and the Auditory, Intellectually, and Repetition (AIR) learning model.  In addition, this study also aims to reveal the shortcomings in the singing method in the madrasah.  From the existing searches, it was found that the learning steps in the madrasah reflected the Auditory, Intellectually, and Repetition (AIR) learning model.  In addition, it is revealed that the students understand better when the meaning of Arabic is transmitted into Indonesian.